The Production and Consumption of Drinking Water in the City of Ranya: A Study in Economic Geography (Raparin Journal of Humanities (RJH), 2025)
Due to their critical role in preserving human life and all living beings, investigating water resources is essential. The district of Ranya which belongs to Sulaymaniyah faces lack of drinking water, specifically in the summer. The city basically relies on natural sources such as rainfall, surface water, and groundwater to fulfill its water necessities. The overall production capacity of drinking water filtration system and production facilities in Ranya in 2023 attained nearly 0.36 million cubic meters per day, or 131 million cubic meters annually. Qula water resource represented 92% of this total, whereas the rest 8% was provided by other resources across the city. This study applies a methodology grounded in fundamental ideas of economic geography namely production, utilization, and exchange. The researcher used cartographic, statistical, and fieldwork methods, together with an investigation of the existing state surrounding water-related issues in the region. The main objective is to examine the distribution of drinking water sources in Ranya, evaluates the everyday distribution provided to citizens, and assess its acceptability for consumption. The research applies fundamentalist, regional, and conduct-based frameworks to offer a comprehensive understanding of the issue. Findings show that water use and conservation in Ranya are neither systematically organized nor strategically planned. There is absence of rationalized consumption and no standardized system for the allocation and removal of water in the city.